(untitled) (Annals of Medical Research, 2021)
Aim: Psoriasis is a skin disease with metabolic and cardiac comorbidities. Adropin is a peptide hormone which is thought to play a role in metabolic diseases, energy homeostasis, endothelial function and cardiac diseases in recent years. In this study, we aimed to evaluate adropin levels in psoriasis patients Materials and Methods: The study included 51 plaque psoriasis patients aged 18-65 years who had no systemic disease and had not received systemic treatment in the last three months and 37 healthy controls matched by sex, age and body mass index (BMI). Serum adropin, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), and triglyceride (TG), fasting blood glucose (FBG), fasting serum insulin, BMI, systolic blood pressure (SBP) and diastolic blood pressure (DBP) values were recorded. Results: Serum adropin level was 73.04 ± 46.21 pg / ml in the patient group. In the control group, serum adropin level was 77.26 ± 43.69 pg / ml. Serum adropin levels were lower in the patient group, but this was not statistically significant (p = 0.667). PASI value was negatively correlated with serum adropin level. There was no correlation between serum adropin level and other variables. Insulin level, Homa-IR level, systolic and diastolic pressure were significantly higher in the patient group (p <0.05). Conclusion: In our study, although adropin levels were not significantly lower in the patient group, we concluded that this may be associated with low PASI values. The role of adropin in psoriasis vulgaris will emerge with further studies.